Relación entre el clima organizacional y el síndrome de burnout - Tupayachi Llaque, María José (2022)
The organizational climate is the state of mind of an organization, when the organizational climate is positive, it generates motivation, high performance, physical and mental health, among other benefits for the company and the worker himself; when the organizational climate is negative, it can trigger the appearance of Burnout syndrome in collaborators. The objective of this systematic review is to identify the relationship between the organizational climate and Burnout syndrome. To achieve the objective, the recommendations of the PRISMA statement (Page et al., 2020) were applied and a search was carried out in the Ebsco, Apa PsycNET, Proquest and Scopus databases, the investigations were selected for analysis. who met the inclusion and exclusion criteria (n=10). As a result, there is a significant negative connection (Buckey et al., 2021; Hashimoto et al., 2021; Jeung et al., 2021; Lan et al., 2021; Lee et al., 2018; Ren et al., 2020; Tsukamoto et al., 2020; Yslado et al., 2021; Yu et al., 2019; Žutautiene et al., 2020) between organizational climate and Burnout syndrome. It is concluded then that a positive organizational climate, especially if it is a collaborative environment, turns out to be a protective factor, which minimizes and even prevents the appearance of Burnout syndrome.